Faktor-Faktor yang Memengaruhi Auditor Switching Pada Perusahaan Manufacture Sektor Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesia Tahun 2017 – 2021 - Reny Aziatul Pebriani; Leriza Desitama Anggraini; Harsi Romli; Lily Syafitri (Universitas Indo Global Mandiri, 2022)
This study aims to determine how much influence the growth of company size management turnover and audit delay on auditor switching in the basic and chemical industry sectors listed on the Indonesia Stock Exchange 2017-2021. This type of research is associative research. Samples were taken using purposive sampling technique. The sample is 40 companies from 79 basic and chemical industrial sector companies listed on the Indonesia Stock Exchange (IDX). The research period used was 5 years (2017-2021) so that the research data analyzed amounted to 200. The data analysis techniques used were descriptive statistics and logistic regression.Based on the results of this study indicate that (1) the company's growth partially has no positive and significant effect on auditor switching, this is indicated by the regression coefficient of the company's growth variable of 0.000 and the significance value of company growth is 0.974, (2 ) Management change partially has a positive and significant effect on auditor switching, this is indicated by the regression coefficient of management turnover variable of 1.150 and the significance value of management change is 0.035, (3) Company size partially has a negative effect and does not significant effect on auditor switching, this is indicated by the regression coefficient of the firm size variable of -0.036 and the significance value of firm size of 0.770, (4) Audit delay partially has no positive and significant effect on auditor switching, this is indicated by the regression coefficient of variance the audit delay bell is 0.003 and the audit delay significance value is 0.422, and (5) company growth, management turnover, company size and audit delay simultaneously have no significant effect on auditor switching, this is indicated by the significance value of 0.326.